Maqāṣid Al-Sharī‘at: The Main Reference and Ethical-Spiritual Foundation for the Dynamization Process of Islamic Law - Iffatin Nur; Syahrul Adam; M. Ngizzul Muttaqien (Universitas Islam Negeri Jakarta, 2020)
The two primary and significant roles of maqāṣid al-sharī‘at worth studying are directive and defensive systems. The directive system, for instance, puts the maqāṣid al-sharī‘at as the main reference for any reformation or changing processes and dynamization of the Islamic law, whereas the latter places it as the supreme principle of morality that provides the foundation and ethical-spiritual power for Muslim Societies when they interact with the law. With these two roles, the maqāṣid al-sharī‘at can serve as a driving force to create future changes towards a more constructive and humanistic society. This study is library research which examines the maqāṣid al-sharī‘at from the time of Prophet Muhammad (Peace be Upon Him) to this very day. It aims at elaborating the position of maqāṣid al-sharī‘at as the primary reference and ethical-spiritual foundation for the dynamization process of Islamic law in dealing with contemporary issues. It also examines the concept of maqāṣid al-sharī‘at and analyzes the flexibility, adaptability, and dynamic of Islamic law. In addition, it is intended to open the mind of those who claim that Islamic law is so immutable, doctrinal, eternal, and final. This means that Islamic law is assumed to be inadaptable to various forms of social changes and modernization. AbstrakPeran paling utama dan penting maqāṣid al-sharī‘at yang patut dipelajari adalah sistem direktif dan pertahanan. Sistem direktif, misalnya, menempatkan maqāṣid al-sharī‘at sebagai rujukan utama untuk setiap reformasi atau proses perubahan dan dinamisasi hukum Islam, sedangkan yang terakhir menempatkannya sebagai prinsip moralitas tertinggi yang memberikan landasan dan kekuatan etis-spiritual untuk masyarakat Muslim ketika mereka berinteraksi dengan hukum. Dengan dua peran tersebut, maqāṣid al-sharī‘at dapat menjadi pendorong perubahan masa depan menuju masyarakat yang lebih konstruktif dan humanistik. Penelitian pustaka ini meneliti maqāṣid al-sharī‘at dari masa Nabi Muhammad Saw. hingga hari ini. Hal ini bertujuan untuk menguraikan posisi maqāṣid al-sharī‘at sebagai acuan utama dan landasan etis-spiritual bagi dinamisasi proses hukum Islam dalam menghadapi persoalan kontemporer. Ini juga mengkaji konsep maqāṣid al-sharī‘at dan menganalisis fleksibilitas, kemampuan beradaptasi, dan dinamika hukum Islam. Selain itu, dimaksudkan untuk membuka pikiran mereka yang menyatakan bahwa hukum Islam begitu lestari, doktrinal, abadi, dan final sehingga dianggap tidak dapat beradaptasi dengan berbagai bentuk perubahan sosial dan modernisasi yang membawa banyak isu kekinian.